2011
DOI: 10.1159/000330849
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation Improves Cognitive and Psychomotor Functions in Adult Hemodialysis Patients

Abstract: Background: Kidney failure is believed to have a negative impact on cognitive function, and cognitive impairment is common among maintenance hemodialysis (HD) patients. Previous studies have shown a beneficial effect of kidney transplantation in certain cognitive tests but not across all cognitive domains assessed. But, most of these studies performed a cross-sectional analysis, suffered from lack of standardization of adequate dialysis dose, hemoglobin level, and insufficient sensitivity of neuropsychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 50 publications
1
52
2
1
Order By: Relevance
“…18 In patients undergoing peritoneal dialysis, the few available data suggest that the prevalence of cognitive impairment might be lower than in hemodialysis patients. 19,20 However, this apparent discrepancy may reflect selection bias (because the dialysis procedure will depend on the patients' characteristics and thus cognitive function before the introduction of dialysis 21 ) rather than the procedure's characteristics per se.…”
Section: Patients With Stage 5 Ckdmentioning
confidence: 99%
“…18 In patients undergoing peritoneal dialysis, the few available data suggest that the prevalence of cognitive impairment might be lower than in hemodialysis patients. 19,20 However, this apparent discrepancy may reflect selection bias (because the dialysis procedure will depend on the patients' characteristics and thus cognitive function before the introduction of dialysis 21 ) rather than the procedure's characteristics per se.…”
Section: Patients With Stage 5 Ckdmentioning
confidence: 99%
“…132 Cognitive function after renal transplantation Several studies have identified an improvement in cognitive function shortly after renal transplantation. [133][134][135] An improvement in cognitive function seems to be long term, with studies showing maintained cognitive performance after 2 years. 135 This observation is in contrast to the decline in memory performance reported in matched dialysis patients who do not undergo transplantation.…”
Section: Cognitive Impairment In Uraemiamentioning
confidence: 99%
“…[133][134][135] An improvement in cognitive function seems to be long term, with studies showing maintained cognitive performance after 2 years. 135 This observation is in contrast to the decline in memory performance reported in matched dialysis patients who do not undergo transplantation. 135 Memory impairment typically resolves 1 year post-transplantation, whereas improvement in cognitive domains of attention, motor skills, visual planning, psychomotor speed, and abstraction, can occur immediately and typically remain stable.…”
Section: Cognitive Impairment In Uraemiamentioning
confidence: 99%
“…Also in accordance with this finding of high relevance of tight control of kidney function and CKD-associated risk factors and diseases for the prevention of progression of cognitive deficits is the positive effect of dialysis and transplantation therapy on cognition [24]. For hemodialysis patients it is important to consider the timing of neuropsychological examination.…”
Section: Introductionmentioning
confidence: 54%
“…Within one session, there was a significant improvement from immediately before dialysis to upon completion time in hemodialysis patients while there was no significant change in the CAPD group [26]. However, kidney transplantation is the therapy of choice in end-stage renal disease and should usually be preferred over hemodialysis because cognition mostly improves after successful kidney transplantation compared with previous adequate hemodialysis [24]. In the increasing number of elderly patients desiring kidney transplantation, the benefits of improved cognitive outcomes after transplantation due to partly reversion of underlying mechanisms have to be traded off against the risk of surgery as well as side-effects or complications of immunosuppressive medication [27].…”
Section: Introductionmentioning
confidence: 98%